2020
DOI: 10.3389/fcimb.2020.00329
|View full text |Cite
|
Sign up to set email alerts
|

Bromodomain Inhibitors as Therapeutics for Herpesvirus-Related Disease: All BETs Are Off?

Abstract: Although the ubiquitous human herpesviruses (HHVs) are rarely associated with serious disease of the healthy host, primary infection and reactivation in immunocompromised individuals can lead to significant morbidity and, in some cases, mortality. Effective drugs are available for clinical treatment, however resistance is on the rise such that new anti-viral targets, as well as novel clinical treatment strategies, are required. A promising area of development and pre-clinical research is that of inhibitors of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…This view is comparable with observations using Epstein-Barr virus (EBV), which showed that treatment with the I-BET JQ1 during lytic EBV infection limited the virus life cycle in two ways: preventing expression of the EBV IE protein BZLF1 but also inhibiting interaction of BRD4 with the origin of lytic replication (oriLyt) ( 53 ), consistent with our use of the BRD4-degrader dBET1. Thus, despite possible different mechanisms, the restriction of HCMV reactivation by I-BETs might allow safer treatment of already immunocompromised patients ( 24 ). Cotreatment with GSK726 and CHR-4487 still induced reactivation and virus replication, likely due to HDACis aiding virus DNA replication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This view is comparable with observations using Epstein-Barr virus (EBV), which showed that treatment with the I-BET JQ1 during lytic EBV infection limited the virus life cycle in two ways: preventing expression of the EBV IE protein BZLF1 but also inhibiting interaction of BRD4 with the origin of lytic replication (oriLyt) ( 53 ), consistent with our use of the BRD4-degrader dBET1. Thus, despite possible different mechanisms, the restriction of HCMV reactivation by I-BETs might allow safer treatment of already immunocompromised patients ( 24 ). Cotreatment with GSK726 and CHR-4487 still induced reactivation and virus replication, likely due to HDACis aiding virus DNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we show that continuous treatment of latently infected cells with certain HDACis causes not just activation of HCMV gene expression but full reactivation and lytic cascade of the virus. In contrast, through the release of the cellular transcriptional activating complex positive-transcription elongation factor-b (P-TEFb) from repressive BRD4-associated aggregates, and recruitment via the superelongation complex (SEC) to viral promoters, inhibitors of the BET family of bromodomain (BRD)-containing histone acetylation mark reader proteins (I-BETs) ( 24 , 25 ) induce dysregulated HCMV gene expression. This allows production of virus lytic immunogens, including immunodominant IE72, pp65, and gB, while restricting the expression of many viral immunomodulating proteins (e.g., MHC class I/II downmodulators US2, 3, 6, 8, and 11) and, most importantly, virus DNA replication machinery (e.g., UL44, UL112).…”
mentioning
confidence: 99%
“…Due to the fact that the bromodomain-containing proteins act as epigenetic modulators controlling both cellular functions and the viral life cycle (19) their targeting (especially the targeting of BRD4) via small molecule inhibitors has emerged as a potent therapy for viral infectious diseases (19,23,50,54,60).…”
Section: Discussionmentioning
confidence: 99%
“…The severe acute respiratory syndrome-coronavirus (SARS-CoV-2) emerged in China at the end of December 2019. Globally, as of 19 th January, 2021 there have been 94.124.612 confirmed cases of the coronavirus disease 2019 (COVID- 19), including 929.994 deaths reported to WHO (https://covid19.who.int/). The clinical presentation of COVID-19 is diverse, ranging from asymptomatic infection to mild upper respiratory tract illness to severe interstitial pneumonia with respiratory failure and death (31).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the “block and lock” paradigm aims to push latent HIV reservoirs into tight latency through inhibition of Tat-dependent transcription [ 17 , 174 ]. Epigenetic drugs have also been tested in the context of other chronic viral infections, such as in the use of bromodomain and extra-terminal domain (BET) inhibitors to target HPV and herpesvirus infections [ 175 , 176 ]. Similarly, inhibitors of lysine-specific histone demethylase 1 (LSD1) and PRC2 enzymatic subunit EZH2 have been shown to blunt HSV-1 reactivation [ 98 , 177 , 178 ].…”
Section: Outlook For Epigenetic-directed Therapeutic Interventions For Viral Infectionsmentioning
confidence: 99%